The curious case of vandals: Brazil's environmental and regional policies in the Bolsonaro years. - Sawicka, Monika (Third World Quarterly, 2025)
This paper aims to contribute to the debate on foreign policy strategies of state actors in the international system with a particular focus on policies pursued by far-right populist leaders. On the theoretical level, it builds on role theory and status-seeking strategies drawn from social identity theory (SIT) to offer an enhanced conceptual framework suitable for scrutinising more radical forms of international activism. The theoretical points are then illustrated empirically by exposing the findings from content analysis of Brazilian policymakers' speeches and their juxtaposition with the Bolsonaro government's policies in the areas of environmental protection and regional cooperation. The author's main claim is that President Jair Bolsonaro and his Foreign Affairs Minister Ernesto Araújo, through their rhetoric about cooperation in South America and the Amazon and the actions undertaken by the administration in these fields, envisioned for Brazil the role of vandal. This had substantial consequences for the country's international standing.